?GRAIN YIELD AND YIELD ATTRIBUTES OF BORO RICE AS AFFECTED BY CULTIVAR ANDWEEDING REGIME IN HAOR AREA (Biological Sciences - PJSIR, 1998)
An experiment wa conducted in the farmers' field in the haor of Jawar village of Kishoreganj district, Bangladesh during the period November 1987 to April 1988. Three adjacent fields from three different farmers were taken for the experiment and each field was considered as a replication. Two factors included in the experiment were cultivar and weeding regime. The experiment was laid out in a split plot design where cultivars were assigned in the main plot and weeding regime in the sub plot. Results showed that BR3 produced the highe t and Ketehli boro the lowest yield. Other five varieties commonly cultivated in the area yielded in between them and four of them had statistically similar yield. Cultivar and weeding regime interaction indicated that BR3 and Hazisail produced the highest yield under weed-free situation. Farmers' common weeding practice has the scope of further improvement.